Using portfolio assessment to improve EFL students’ expository-writing performance - Waode Nur Gita Dahviyanti; Iskandar (International Journal of Humanities and Innovation (IJHI), 2019)
The objectives of the research were to find out the extent to which the use of portfolio assessment improves EFL students’ performances in expository-writing and to find out the students’ responses about the taking of portfolio assessment in improving their performance in writing expository text. The researcher applied classroom action research which was done through two cycles. The location of this research was at one of the secondary schools in Makassar, South Sulawesi, Indonesia. There were 31 students as a sample in this research and the data were collected using observation, writing test, interview, and analyzed by using descriptive statistics. The result showed that portfolio assessment had improved EFL students’ expository-writing performance. The students were better in arranging the words into sentences and paragraph in order to convey their ideas, opinions, and feeling because they had already known the steps in the writing process, and they learned from their previous evaluated portfolios, and their responses on the using of portfolio assessment as a method in writing expository process was positive. They got positive motivation and appreciation to progress their writing performance. They were excited to revise and edit their draft to become the best work in every meeting.